An Improved Retransmission Approacb Based on Opportunistic Network Coding in Multicast Networks - Pengfei Shao; Yanwei Zhao; Yaohui Wu; Xinwei Yao (Dianxin kexue)
A novel opportunistic-network-coding-based retransmission approach was proposed.According to the feedback on packet loss from the receiving nodes,this novel approach can not only efficiently select a combination of lost packets through Hash lookup for packet retransmission,but also can ensure priority retransmission making up to a single combination retransmission packet which can maximize the number of receiving nodes for recovering their lost packets.Furthermore,the proposed approach fully exploits the coding opportunity based on neighborhood association,and allows the receiving nodes to recover their lost packets from multiple retransmission packets.The simulation results show that this novel approach can effectively reduce the number of retransmissions to improve the transmission efficiency with respect to the existing algorithms.